A new species of Isoetes (Isoetaceae) from Turkey, with a study of microphyll intercellular pectic protuberances and their potential taxonomic value - Rolleri, Cristina Hilda (2005)
Isoetes anatolica sp. nov. is described from a population growing in seasonal ponds of a mountain near the southern coast of the Black Sea in Bolu, Turkey. It is a robust, amphibious quillwort, characterized by semiterete, carnose microphylls, semicircular foliar section, smooth cuticle, prominent cuticular pegs, stomata, several collenchymatous strands, abundant pectic filaments and connections in the cells of the translacunar diaphragms, incurved alae, well developed ligula, small carnose labium, no velum, well-formed bulliform megaspores and obscurely muriform microspores. Plants were investigated anatomically and a description with additional diagnostic characters is included. Morphological affinities with other species of the genus are discussed. Intercellular pectic protuberances (IPP) were studied in the cells of the translacunar diaphragms of the microphylls of several species of Isoetes including I. anatolica. The IPP were examined to determine if they could provide diagnostic characters. They were detected with TBO and analysed using light and scanning electron microscopy. Types of IPP and species bearing them were as follows: warts in I. adspersa, I. andina, I. boliviensis, I. duriei, I. engelmannii, I. lechleri, I. longissima, I. melanopoda, I. storkii, I. velata. ssp. velata, and I. velata ssp. asturicense; warts and filaments in I. brochonii, I. lacustris, and I. setacea, and connections in I. anatolica and I. malinverniana. IPP are lacking in I. boryana, I. echinospora, I. histrix and I. novogranadensis. Combination of type, density, and distribution of IPP promises to be a useful vegetative character in a genus in which diagnostic characters are scarce.